Analysis of Thermal Evolution of Si2U3/Al Calcined Miniplates - Arboleda Zuluaga, Paula Andrea (2015)
As part of a process called cerus for the conditioning of spent fuel elements from research reactors (which is about itsimmobilization in a sintered ceramic matrix of uranium oxide) were performed calcinations and sintering on an aluminumminiplate that representing a real plate from MTR fuel type, but containing natural Si2U3 instead of enriched. Product of heattreatments it results a complex multi-phase material, it was studied its behavior during and after heat treatments involved in thecerus process. There were performed differential thermal analysis (DTA) in air to 1250 °C, and X-ray diffraction at hightemperature (700-1100 °C) to elucidate which compounds were generated during the calcination and sintering and the momentwhen these transformations occur, and as a result there were obtained complex alloys of Al-U, and the formation of oxides ofaluminum and uranium. On the other hand, tests were carried out on compacted powder of calcined miniplates in a hightemperature microscope (HSM) and dilatometry to know their linear and surface response to the heating and sintering in order tocharacterize their individual contributions to the final material, resulting in an important expansion of about 25% which wasattributed to oxidants interactions and/or formation of uranium aluminides and silicides. Several intermetallic of Si-U and Al aswell as the generation of oxides of aluminum and uranium were found.